Aplikasi E-Pembelajaran Jom Kenali Malaysia bagi Pelajar Sekolah Rendah Tahun 1 - Zazyawi, Siti Zaimira; Mohd Nawi, Nazri (Applied Information Technology And Computer Science, 2021)
Jom Kenali Malaysia application is an android application with E-learning concept developed to help year 1 primary school students to learning the general knowledge about the states in Malaysia. The general knowledge about states in Malaysia is contained in this application are the flag, state capital, state position on the map, sultan and the official anthem of each state in Malaysia. This application was developed to help students who are less interested used textbooks in learning the states in Malaysian and still no alternatives such as the development of applications about Malaysia in the Play Store also causes in the production of this application. The prototype model are used in the methodology development. Meanwhile, in application development is using Android Studio software with Java programming language and Firebase database. The application also uses an object -oriented approach. The development of this Jom Kenali Malaysia application will give the benefit to many users. The benefit is to reduce the problems faced by primary school students in year 1. Besides that, teachers and parents can also use this application in learning and recognizing the general knowledge of the states in Malaysia. At the end of this project, an android application with the concept of e-learning was successfully developed and can provide benefits to  year 1 primary school students in learning the states of Malaysian.